2003
DOI: 10.1086/378676
|View full text |Cite
|
Sign up to set email alerts
|

Virological and Immunological Impact of Tuberculosis on Human Immunodeficiency Virus Type 1 Disease

Abstract: Unlike other opportunistic infections associated with human immunodeficiency virus (HIV) type 1, tuberculosis (TB) occurs throughout the course of HIV-1 infection, and, as a chronic infection, its impact on viral activity is sustained. In dually infected subjects, HIV-1 load and heterogeneity are increased both locally and systemically during active TB. Studies over the past decade have indicated that Mycobacterium tuberculosis (MTB) infection supports HIV-1 replication and dissemination through the dysregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
99
1
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(113 citation statements)
references
References 87 publications
5
99
1
4
Order By: Relevance
“…Additionally, observational data have shown a higher level of systemic HIV heterogeneity in HIV-TB-coinfected patients than in CD4-matched HIV-infected patients without active pulmonary TB (55). It is thought that the increased proinflammatory response with active TB plays a role in increasing HIV transcription, as higher levels of tumor necrosis factor alpha (TNF-␣) are associated with higher viral loads in patients coinfected with HIV and TB (245). On the other hand, the treatment of active TB did not show a significant difference of CD4 counts or HIV viral load in a prospective cohort of 111 TB-HIV-coinfected patients in South Africa (197).…”
Section: Effect Of Tuberculosis On Hivmentioning
confidence: 99%
“…Additionally, observational data have shown a higher level of systemic HIV heterogeneity in HIV-TB-coinfected patients than in CD4-matched HIV-infected patients without active pulmonary TB (55). It is thought that the increased proinflammatory response with active TB plays a role in increasing HIV transcription, as higher levels of tumor necrosis factor alpha (TNF-␣) are associated with higher viral loads in patients coinfected with HIV and TB (245). On the other hand, the treatment of active TB did not show a significant difference of CD4 counts or HIV viral load in a prospective cohort of 111 TB-HIV-coinfected patients in South Africa (197).…”
Section: Effect Of Tuberculosis On Hivmentioning
confidence: 99%
“…The course of HIV infection is accelerated subsequent to the development of TB and the inverse relationship between HIV viraemia and CD4+ count gets shifted to the right. 1 Compared with CD4+ count-matched HIV-infected controls without TB, the relative risk of death and development of other Infections is higher in HIV-TB coinfected patients.…”
Section: Introductionmentioning
confidence: 97%
“…2 Moreover, HIV increases the vulnerability to both new infection and reinfection, the likelihood of reactivation, and the progress from latent TB infection to active disease. 5,6 An earlier study demonstrated that HIV-infected individuals co-infected with TB have a 5-15% annual risk and a 50-60% lifetime risk of developing TB disease compared with HIV-uninfected individuals, who have only a 10% lifetime risk. 3 HIV-infected children, especially those with low CD4 + cell counts, demonstrate greater morbidity from TB than do HIV-uninfected children, because of atypical manifestations, increased tendency for extrapulmonary TB (EPTB) and disseminated TB, 7,8 rapid disease progression, 9 and suboptimal treatment responses.…”
Section: Introductionmentioning
confidence: 99%